Canine flea control: too much choice?. (2nd October 2019) - Paterson, Sue
Abstract : Ectoparasite control forms an important part of any routine canine health programme but is also an integral part of the management of pruritic skin disease in the dog. As such it is important that veterinary surgeons are aware of the life cycle of the flea and the mode of action of the numerous flea control products that are currently available. The suitability of a product may be different depending on the health status of the dog and concurrent therapy. This article considers the most important groups of flea control products.